Investigating Farmers’ Preferences For Crop Insurance Product Attributes in Indonesia Using The Bayesian Best-Worst Method - Rachman, Muhammad Ibrahim; Nuryartono, Nunung; Arifin, Bustanul; Bakhtiar, Toni (Jurnal Manajemen dan Agribisnis, 2024)
Background: In 2015, the government of Indonesia launched a crop insurance program to anticipate the economic impact of crop failure on farmers due to the climate crisis. Despite the government's high premium subsidy, farmers' participation rate in crop insurance remains very low. Therefore, a study is needed to determine which product attributes in an agricultural insurance product are important to farmers and can affect their participation rate. Purpose: This study aims to investigate the factors that farmers consider when selecting a crop insurance product. Design/methodology/approach: The study focuses on the features of the Rice Farm Insurance (AUTP) product: total sum insured, product type, premium, risk coverage, and claim. The research was conducted by sending questionnaires to 110 farmers in 15 villages in Sliyeg, Indramayu. The Bayesian Best-Worst Method was used to analyze the data. Using a scale from 1 to 9, the best and worst criteria are compared pairwise.Findings/Result: The findings indicated that the total sum insured is the most crucial consideration for farmers when choosing a crop insurance product, followed by the premium, risk coverage, terms of claims, and product type. The top two positions of the product attributes are finance-related, indicating a need for improved understanding of agricultural risk management among farmers, extending beyond dollar amount, through continuous education. With the findings in this study, the government and other stakeholders need to develop effective strategies to increase farmers' awareness of the importance of insurance in managing their business risks. This study's added value comes from convincingly showing that farmers prioritize the amount of sum insured over premiums and other aspects. Other researchers can use this research as a springboard to learn more about the importance of product attributes in creating crop insurance products.Conclusion: The top two positions of the product attributes are finance-related, indicating a need for improved understanding of agricultural risk management among farmers, extending beyond dollar amount, through continuous education. With the findings in this study, the government and other stakeholders need to develop effective strategies to increase farmers' awareness of the importance of insurance in managing their business risks.Originality/value (State of the art): This study's added value comes from its convincingly showing that farmers prioritize the amount of sum insured over premiums and other aspects. Other researchers can use this research as a springboard to learn more about the importance of product attributes in creating crop insurance products. Keywords: climate crisis, crop insurance, Bayesian best-worst method, multi-criteria decision making, farmer preference